The Development of Inner-City Inclusionary Housing: The Case of Cape Town - Knight, Jason (Department of Construction Economics and Management, 2023)
This minor dissertation investigates the challenges experienced by private sector developers in supplying inner-city inclusionary housing and explores possible interventions by the state to overcome these challenges to advance such developments. This research used a case study method with various primary and secondary data collection techniques such as a literature review, precedent analysis, development appraisal and semi-structured interviews. The data analysis was undertaken using pattern matching and descriptive statistics. The research findings put forward specific state interventions such as inclusionary zones, pro-active up-zoning, area medium income, in-lieu fees, density bonuses, fast tracking planning applications, access to subsidies, making well-located public land available, and access to infrastructure. The most significant context appropriate intervention identified was the need to fast track statutory approval processes for inclusionary housing development applications, density bonus and making well-located public land available at a reduced price to assist private developers to supply inclusionary housing developments in inner-city areas such as Cape Town, South Africa.